1993
DOI: 10.1002/eji.1830231225
|View full text |Cite
|
Sign up to set email alerts
|

Switching capacity of FcϵRII‐positive and ‐negative murine B cells

Abstract: In previous studies, our laboratory demonstrated the utility of the low affinity IgE Fc receptor (Fc epsilon RII) in delineating a number of murine B cell subsets. In the spleen, the Fc epsilon RII is expressed on mature conventional B cells but is absent on marginal zone B cells. In the peritoneal cavity, the receptor is present on all conventional B cells, but is not expressed on fresh peritoneal Ly1/sister B cells. The studies in this report compared the ability of these B cell populations to isotype switch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…A significant difference between the response of splenic and peritoneal B cells to IL-5 has been reported (27)(28)(29). We observed simultaneous generation of B1-IgE + cells in the spleen and in the peritoneal cavity during the acute phase of the disease when the overall pattern of the immune response is Th2-dominated.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…A significant difference between the response of splenic and peritoneal B cells to IL-5 has been reported (27)(28)(29). We observed simultaneous generation of B1-IgE + cells in the spleen and in the peritoneal cavity during the acute phase of the disease when the overall pattern of the immune response is Th2-dominated.…”
Section: Discussionsupporting
confidence: 58%
“…In vitro, the induction of IgE switch in B1 cells has been shown to be difficult, requiring very high levels of cytokines (29), in studies based on the production of IgM, IgG1, IgE, and IgA by B1 (CD23 -) and B2 lymphocytes (CD23 + ). Both subpopulations were obtained by sorting from the spleen and peritoneal cavity and cultured with lipopolysaccharide and IL-4.…”
Section: Discussionmentioning
confidence: 99%
“…The biological function of Thy1 is poorly understood, but it may likely be involved in signal transduction from the plasma membrane, because it was shown that thymocytes of Thy1-deficient mice exhibit augmented TCR signaling and impaired T cell differenti-ation (30). Other studies showed that LPS+IL-4-stimulated B cells, but not LPS-stimulated B cells, upregulate Thy1 (31,32). We confirm and extend these findings by showing that STAT6 expression in B cells is required for this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Although the B220 ϩ CD23 Ϫ splenic subset contains immature as well as marginal zone B cells, the former is only a minor constituent of this population (7). BALB/c mice were used for isolating peritoneal B cell subsets because of the relatively high proportion of B1 B cells (10). Fig.…”
Section: Proliferative Response Of B Cell Subsets Stimulated With Rcd40lmentioning
confidence: 99%
“…Detailed studies by Rothstein and coworkers (11, 14 -16) have demonstrated B1 B cells to exhibit constitutively elevated levels of protein kinase C and nuclear activated STAT3, and to have decreased activation of phospholipase C-␥2 and NF-B after anti-IgM treatment. When assessing the ability of B1 and B2 B cells to differentiate and isotype switch upon culture with LPS plus cytokines, B2 B cells were found to produce high levels of IgM, IgG, and IgE, while B1 B cells secreted only high levels of IgM (5,10,17). The latter subset produced low levels of IgG and little or no IgE (5,10,17).…”
mentioning
confidence: 99%